IMPLEMENTATION OF AN ELECTRONIC MEDICAL RECORD SYSTEM FOR LAFENE HEALTH CENTER’S ATHLETIC TRAINERS - Gallagher, Jamie Elizabeth (My University, 2019)
Electronic medical records (EMRs) are important tools that allow medical care professionals to communicate. One aspect of the healthcare industry that has not been frequently studied is the communication between athletic trainers who work with recreation athletes and physicians in a university setting. Through my Applied Practice Experience at Lafene Health Center at Kansas State University, I implemented an EMR system in order to improve the communication of recreation athlete injuries evaluated by an athletic trainer and the physicians who provide follow up care. I evaluated the initial and potential impact of the implementation of the EMR system for both clinicians and patients. I collected qualitative data through interviews with athletic trainers and physicians who were involved with the implementation process. Additionally, quantitative data were collected to investigate if there was a change in documented athletes and corresponding follow up rates. The results suggested implementation of this EMR elicited an increase in communication between athletic trainers and physicians. Consequently, physicians reported more efficient evaluations because of known injury history. Furthermore, doctors were able to spend more time discussing injury education and treatment plans within an appointment because of additional time. Athletic trainers were also able to assist athletes more effectively by providing them with injury and rehabilitation handouts through the EMR. This EMR created a more cohesive communication environment for the medical staff involved with the evaluation and treatment of recreation athletes at Kansas State University.
Keywords: medical records; electronic; public health; EMR